The Application Of Structurally Controlled Geostatistics To The Hilton Orebodies, Mt. Isa, Australia (Society for Mining, Metallurgy & Exploration, 1989)
The purpose of this paper is to describe two systems designed to provide estimations in stratigraphic orebodies for the purposes of detailed mine planning. The first is a completely geostatistical approach and the second is a combined geostatistical/deterministic approach. The essential features of both systems are the estimation of stratigraphic ore boundaries and the subsequent use of those boundaries to provide stratigraphic (or zonal) control for block and point grade estimation (kriging). Both systems are illustrated by application to a section of, the Hilton orebodies, Queensland, Australia.